2013
DOI: 10.1088/1674-4926/34/3/032002
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of GaAs

Abstract: We have investigated the optical properties of gallium arsenide (GaAs) in the photon energy range 0.6-6.0 eV. We obtained a refractive index which has a maximum value of 5.0 at a photon energy of 3.1 eV; an extinction coefficient which has a maximum value of 4.2 at a photon energy of 5.0 eV; the dielectric constant, the real part of the complex dielectric constant has a maximum value of 24 at a photon energy of 2.8 eV and the imaginary part of the complex dielectric constant has a maximum value of 26.0 at a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Using measured reflectivity values, and solving for n 2 in Eq. 1, index of refraction values of 4.1 and 3.9 were obtained for GaAs and molybdenum, respectively, in reasonably good agreement with published values, 4.0 and 3.75 [26,27]. The published index of refraction for CsK 2 Sb is 3.6 [28] and would provide a reflectivity of about 32%, assuming a smooth photocathode surface, a purely specular reflection, and ignoring the possibility of enhanced reflectivity due to multiple internal reflections within the photocathode thin film.…”
Section: Photocathode Characteristicssupporting
confidence: 89%
“…Using measured reflectivity values, and solving for n 2 in Eq. 1, index of refraction values of 4.1 and 3.9 were obtained for GaAs and molybdenum, respectively, in reasonably good agreement with published values, 4.0 and 3.75 [26,27]. The published index of refraction for CsK 2 Sb is 3.6 [28] and would provide a reflectivity of about 32%, assuming a smooth photocathode surface, a purely specular reflection, and ignoring the possibility of enhanced reflectivity due to multiple internal reflections within the photocathode thin film.…”
Section: Photocathode Characteristicssupporting
confidence: 89%
“…It is observed that α(ω) remains almost constant in the energy range 6 -14 eV. The value of absorption coefficient of BaAgP is much larger than that of GaAs (ሺ14-22ሻ×10 4 cm -1 at ~4.8 eV) [69,70] but close to the value for Ba3SbN and Ba3BiN ((120 ×10 4 cm -1 at ~8 eV) [71] and smaller than that of the value for silicon (180×10 4 cm -1 ) [72]. In the visible region, the maximum value of the parallel component of absorption coefficient is 64×10 4 cm -1 and the perpendicular component is 54×10 4 cm -1 .…”
Section: Optical Propertiesmentioning
confidence: 97%
“…Как видно из эксперимента, в ИК-спектре отражения гетерострукту-ры #2 присутствует высокоинтенсивная фононная мо-да (TO + LO) Ga−As с формой, характерной для мо-нокристаллического арсенида галлия, а также низко-интенсивный поперечный оптический фонон TO Al−As от верхнего cup-layer гетероструктуры. Частоты при-сутствующих в спектре продольных LO и попереч-ных TO оптических фононов хорошо согласуются с уже существующими литературными данными [19,20]. Что касается ИК-спектров отражения интегрированных гетероструктур GaAs/Si(100), то следует отметить, что в них также присутствуют фононные колебания Ga−As и Al−Ga.…”
Section: ик-спектроскопияunclassified